DEVELOPMENT OF LIGNITE IN CRETE. COMPARISON OF BASINS, POSSIBILITIES OF EXPLOITATION - Karageorgiou, D. E.; Metaxas Α.; Karageorgiou Μ. Μ. D.; Papanikolaou, G.; Georgakopoulos Α. Ν.; Vrettos, K. (Bulletin of the Geological Society of Greece, 2010)
The island of Crete has been thoroughly explored, by various organizations, for the presence of lignite deposits, in order to examine the possibility of energy independence for the island and thus reduce the cost of consumed electric energy. Research showed that lignite generates in fluvial – lacustrine environments in many places in Crete and lignite deposits have been investigated and exploited from time to time. In the present study all lignite occurrences of the island are recorded and their generation and depositional environment is analysed. Lignite horizons from different basins are compared and correlated. An evaluation of results from previous studies is attempted, regarding both surface information and depth data, derived from borehole projects. Finally, areas suitable for lignite exploitation in the production of electricity or other uses are presented.